Determination of presence iron and manganese in Tasik Chini - Nadiatul Adilah, Ahmad Abdul Ghani; Muhammad Syukri, L. (IOP Publishing Ltd., 2021)
This study investigates the current concentration of heavy metal in Tasik Chini which is iron and manganese. Status of water quality index (WQI) in the rivers at Tasik Chini namely Melai River, Jemberau River, Jerangking River and Gumum River was identified. The water quality results were classified based on the National Water Quality Standard, Malaysia (NWQS). Physical and chemical parameters such as pH, temperature, turbidity, Electrical Conductivity (EC), Suspended Solids (SS), Total Suspended Solids (TSS), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia Nitrogen (NH3-N), Phosphorus (P) were analysed on site and by laboratory experiments. Two types of heavy metals have been tested to determine the concentration of Iron (Fe) and Manganese (Mn) contained in the water samples in Melai River, Jemberau River, Jeranking River and Gumum River using laboratory tools named as Atomic Absorption Spectroscopy (AAS) and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). This (ICP-MS) method is conducting by Central Laboratory in Universiti Malaysia Pahang. Based on the results of the study conducted according to the Water Quality Index (WQI) and National Water Quality Standard, Malaysia (NWQS), the water quality at selected locations which are Melai River, Jemberau River, Jerangking River and Gumum River at Tasik Chini was classified in Class II where conventional treatment are required. According to the results of the study, there are activities conducted around Tasik Chini which have caused water pollution which involves the release of heavy metals. Among the activities identified as the main cause of water pollution in Tasik Chini are iron mining, agriculture, illegal logging and waste disposal.